Incentive regulation of electricity networks under large penetration of distributed energy resources - selected issues - Gert Brunekreeft; Julia Kusznir; Roland Meyer; Madoka Sawabe; Toru Hattori (Jacobs University Bremen, Bremen Energy Research (BER), 2020)
The rapid growth of Distributed Energy Resources (DER) and their integration into network presents currently the greatest challenges for many network operators worldwide in terms of network stability and power quality. To meet these challenges not only huge investment in grid expansion and smart grid technologies is required, but also the network regulation needs to adapt from cost efficiency towards investment and innovation. We analyze the recent experiences with the regulatory framework in several countries facing significant challenges of large penetration of DER. We discuss several selected regulatory issues that are important for promoting needed investment while ensuring cost efficiency, such as the length of regulatory period, X-factor, and allowed rate of return. We conclude that in the era of smart grids, incentive regulation requires a long-term perspective and needs to address the regulatory risks and uncertainties related to investment into grid expansion and smart grid technologies. To do so, incentive regulation should be supplemented by more innovative, investment-friendly regulatory measures. Additional supplementary mechanisms such as output-based regulation would be useful to achieve the regulatory goals and develop fully functional and consumer-oriented smart grid, though details for their implementation still have to be worked out.
Keywords: 330